Pengembangan Pariwisata Berbasis Masyarakat (Community Based Tourism) Di Desa Meat Kecamatan Tampahan Kabupaten Toba - Agnessy Siahaan; Harisan Boni Firmando; Bambang T. J. Hutagalung; Yulia K. S. Sitepu; Ade Putera Arif Panjaitan (Universitas Katolik Widya Karya Malang, 2023)
Meat Village is one of the tourist villages in Tampahan District, Toba Regency. Tourism development is an effort to develop or promote tourist attractions to attract tourists and make tourist attractions more attractive in terms of location and object. The aim of this research is to determine Community Based Tourism Development. Based Tourism), and to find out community empowerment and its role in developing the Meat Tourism Village. The number of informants in this research was 7 (seven) people. This research is a qualitative type of research. Data collection techniques include observation, interviews and documentation. The approach taken is a descriptive approach, based on natural and cultural resources, community groups and village government. The research results show that there are; (a) natural and cultural resources, showing that the village's potential can support the arrival of visitors, (b) community groups to increase community creativity in developing and preserving cultural traditions in Meat Village, (c) the village government which play an important role in efforts to develop the village so that it can attract the attention of tourists if it fulfills the seven charms of tourism, (d) the role of the community who participates in carrying out village activities so that the village remains clean, safe and cool so that anyone who comes to visit can enjoy the tourist attractions is in Meat.